(3JMQjQ GdebGd aj BOGH hCMcGe hahGFO jMJGL EdjgG eDOHh GdCWaGds - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa Medg cJGHg heYdejg CeG HYO , abO hQO Ydi ef HYV UdMGA eDOHi GdCWaGd CSFdI eaNeI OYGfi Pdc Edi LYdgG JCdjakG dWjakG s
(3BNQgG (B:s
(3hCNQi LeGYI Gfg Udi Gddg Ydjg hSde bGd (B: (3jbhd Gddg (B:" (3Ef cfJe JQLhf QMeJi aGQMhG Ndbi Bejf s
(3GdfSNI HgG MhGTs
(3HChdgG Jedec MOjK SfI (B1371s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3HgG fXGe GdJYbjHI s
(3Ydi ghGeTgG HYV GdJUMjMGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs